2022
DOI: 10.1029/2021ef002490
|View full text |Cite
|
Sign up to set email alerts
|

How Does Flow Alteration Propagate Across a Large, Highly Regulated Basin? Dam Attributes, Network Context, and Implications for Biodiversity

Abstract: Dams are a major contributor to flow regime alteration: they increase water residence time, mute peak flows, shift the timing of ecologically important high and low flows, and alter flow periodicity (Poff et al., 2007;Ruhi et al., 2018;Vorosmarty, 1997). These alterations adversely affect riverine and riparian biodiversity because the life-history, morphological, and behavioral adaptations of organisms are often at odds with the novel environmental regime (Bunn & Arthington, 2002;Lytle & Poff, 2004;Mims & Olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 86 publications
2
4
0
Order By: Relevance
“…As found in previous studies (Ferrazzi & Botter, 2019; Ruhi et al., 2019; Singer, 2007), our results highlight the importance of using a suite of signatures. None of the reservoir catchments are above/below the benchmark thresholds for all five signatures, one is picked up by four of the five signatures (the Brenig at the Llyn Brenig outflow; 67003; picked up by all but the WB signature) and 10 catchments exceed the benchmark thresholds for three of the five metrics.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As found in previous studies (Ferrazzi & Botter, 2019; Ruhi et al., 2019; Singer, 2007), our results highlight the importance of using a suite of signatures. None of the reservoir catchments are above/below the benchmark thresholds for all five signatures, one is picked up by four of the five signatures (the Brenig at the Llyn Brenig outflow; 67003; picked up by all but the WB signature) and 10 catchments exceed the benchmark thresholds for three of the five metrics.…”
Section: Discussionsupporting
confidence: 90%
“…Catchments with the highest degree of alteration, or those flagged by multiple signatures, usually also have high contributing area (>70%) and normalized upstream capacity (>0.2). In line with other studies, this finding highlights the importance of a reservoirs size and location for determining the magnitude of flow alteration at a given downstream gauge location (Arheimer et al., 2017; Cipollini et al., 2022; Jumani et al., 2022; Ruhi et al., 2019; Singer, 2007). These catchment descriptors could therefore be useful for environmental flow planning and forecasting significant flow alteration (Grantham et al., 2014).…”
Section: Discussionsupporting
confidence: 88%
“…In the United States (U.S.) alone, more than 90,000 dams change the quantity and variability of natural flow regimes, altering an estimated >85% of inland waterways (National Research Council, 1992). The impacts of such alteration propagate through river networks and affect the fluvial ecosystem in multiple ways: by preventing sediment transport (Willis & Griggs, 2003), by stabilizing channel morphology (Brandt, 2000; Graf, 2006; Topping et al., 2000), by fundamentally changing thermal and flow regimes (Olden & Naiman, 2010; Poff et al., 2007; Ruhi et al., 2019), and by altering the composition and dynamics of aquatic biota (Bunn & Arthington, 2002; Poff et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…More generally, our work provides a broad perspective on the alteration of flow frequencies as a function of dam purpose, residence time, and regional hydroclimate. Detailed watershed‐level research is needed to reduce the hydrologic impacts of dams (Chen & Olden, 2017; Wang et al., 2015), as well as to predict the spatial propagation of flow alteration impacts (Ruhi et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Considerable research has demonstrated widespread consequences of dam operations for riverine hydrology. Dams have been shown to homogenize flows across large spatial scales (Poff et al., 2007), and within a given watershed, flow alteration may accumulate spatially, with downstream sites “inheriting” alteration signatures of upstream dams and tributaries (McManamay, 2014; Ruhi et al., 2022). The assessment of changes within flow classes, or streams sharing similar hydrology (and/or hydrological controls) can help identify patterns of hydrologic alteration due to dam regulation (McManamay et al., 2012).…”
Section: Introductionmentioning
confidence: 99%